Burlesque Connotations in the Pictorial Language in Bronzino’s Poetry - Chiummo, Carla (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
Agnolo di Cosimo, better known as Bronzino, was not only one of the most celebrated painters at the court of Cosimo I in Florence; he was also a dazzling poet, as Vasari reminds us in his Vite. Bronzino was the author of a Petrarchan canzoniere, as well as of burlesque poems. In his sonetti caudati, and in his paradoxical capitoli, burlesque language—characterized by its erotic puns and double meanings—interacts with the pictorial field in a strikingly original way. This interaction hinges on Bronzino’s employment of pictorial discourse: from simple, well-known burlesque symbols and metaphors—the paint brush, colours, bells, or the shapes of mosquitoes, carrots, and cheese—to the subtler use of burlesque topoi to face more serious and complex aesthetic issues.